Foreign Trade of Galicia and Bukovina and Other Austrian Countries at the End of the 19th Century Based on German Railway Statistics - Lipelt, Robert (Studia Historiae Oeconomicae, 2018)
Foreign Trade of Galicia and Bukovina and Other Austrian Countries at the End of the 19th Century Based on German Railway Statistics